Dinuclear Iron(II) Spin‐Crossover Compounds: A Theoretical Study. Issue 20 (30th November 2017) - Phung, Quan Manh; Domingo, Alex; Pierloot, Kristine
Abstract: The structures and spin‐state energetics of two di‐iron(II) complexes based on thiadiazole and oxadiazole ligands in different crystals were studied by using density functional theory and second‐order perturbation theory based on the density matrix renormalization group approach (DMRG‐CASPT2). When taking into account all different contributions to the relative energy, our theoretical approach is capable of providing results that are in excellent agreement with established experimental data. In all cases, we correctly describe the ground state of the complexes as well as predict their spin‐crossover behavior. A comparison between the two complexes in the gas phase and in different crystals shows how the structures change by moving from the gas phase to different crystals and reveals a large impact of the crystal stabilization on the relative spin‐state energy. This theoretical work also demonstrates the applicability of the DMRG‐CASPT2 approach to quantitatively study the spin‐state energetics of multinuclear transition‐metal complexes. Abstract : Crossing spins : Two spin‐crossover dinuclear iron(II) complexes based on thiadiazole and oxadiazole ligands were studied by using DFT and the second‐order perturbation theory (see figure). Experimental results were confirmed by high‐quality calculations. The calculations reveal an enormous impact of the crystal stabilization on the relative spin‐state energy.